Increasing Students' Activeness and Critical Thinking Skills Through the Application of the Deep Learning Integrated Discovery Learning Model to Human Digestive System Materials - Ain, Nurul; Febriantika, Indah; Zuhro, Luluk Faridatus (Actual Insight, 2025)
This research aims to increase students' activeness and critical thinking skills through the application of a discovery learning model integrated with a deep learning approach to the human digestive system. The research method used is Classroom Action Research (PTK) which is carried out in two cycles, involving grade V students in one of the elementary schools in Malang City. Data was collected through observation, critical thinking tests, and documentation of activities, then analyzed descriptively quantitatively. The results of the study showed an increase in student activity from 68% in the first cycle to 85% in the second cycle. The average critical thinking ability of students also increased from 70.2 to 84.5. The integration of Discovery Learning and Deep Learning in this study is carried out by optimizing the stages of data mining and verification of Discovery Learning through deep reflection activities, elaboration of concepts based on real contexts, and analytical discussions that encourage students to reason more deeply on the concept of digestion. This improvement shows that the application of deep learning-based discovery learning can encourage active student involvement while improving critical thinking skills in science learning. The novelty of this research lies in the integration of these two approaches in elementary school learning, which has not been widely implemented in the context of the Independent Curriculum.